“Music Therapy Moments”. Personal Experiences on the Path to a Music Therapy Profession. Scientific opportunities - Magdolna SZABADI (Studia Universitatis Babeş-Bolyai. Musica, 2025)
Becoming a music therapist is shaped by family experiences, group experiences, music learning experiences. In music therapy, the experience is processed analytically, in contrast to music education, where the music is professionally performed and received. Music therapy can be an alternative solution to technical and emotional problems in music education. As an interdisciplinary field, music therapy research is extremely difficult. Changes in a targeted area or skill in the core activity are assessed using the measurement tools used in the core activity. In music education, this can be a developmental experiment. We can use self-developed measurement tools (test, questionnaire) to assess changes along the targeted skills. In teacher training, Scientific Student Association, Erasmus mobility programmes, new courses offers the opportunity to learn music therapy methods and conduct research at international level.